2023
DOI: 10.1093/cid/ciad016
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Immune Response to Severe Acute Respiratory Syndrome Coronavirus 2 Vaccines and Development of Breakthrough Infection in Solid Organ Transplant Recipients: The CONTRAST Cohort

Abstract: Background SARS-CoV-2 vaccination in solid organ transplant (SOT) is associated with poorer antibody response (AbR) compared to non-SOT recipients. However, its impact on the risk of breakthrough infection (BI) should yet be assessed. Methods Single-center prospective longitudinal cohort study enrolling adult SOT recipients who received SARS-CoV2 vaccination during 1-year period from February 2021, and followed-up to April 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 14 publications
1
29
1
Order By: Relevance
“…Furthermore, a fourth vaccine dose resulted in seroconversion in a few more cases. Numerous studies confirmed that a third dose of vaccine increased antibody response against SARS‐CoV‐2 in solid organ transplant recipients 11–13,25–29 . In light of these findings, it became evident that booster vaccine doses would be essential in the prevention strategy against SARS‐CoV‐2.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Furthermore, a fourth vaccine dose resulted in seroconversion in a few more cases. Numerous studies confirmed that a third dose of vaccine increased antibody response against SARS‐CoV‐2 in solid organ transplant recipients 11–13,25–29 . In light of these findings, it became evident that booster vaccine doses would be essential in the prevention strategy against SARS‐CoV‐2.…”
Section: Discussionmentioning
confidence: 95%
“…Recent publications have reported that older age of the recipient 15,16,29 and certain immunosuppressive regimens 16 predispose transplant recipients to severe SARS-CoV-2 infection. In the current study, seronegative status before infection has been proven to be a significant predictor of severe infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, immunocompromized patients with underlying conditions impairing their immune response to vaccines or natural infections are still at increased risk for COVID-19-associated morbidity and mortality. 1,2 States of relative immunologic vulnerability affect the severity of COVID-19, making it crucial to find targeted approaches to manage different levels of clinical complexity. In particular, patients with impaired adaptive humoral immunity have a high risk of prolonged viral shedding, viral rebound, and/or persistent infection.…”
Section: Introductionmentioning
confidence: 99%
“…From the early months of a deadly infection to the present days, the clinical commitment to the SARS‐CoV‐2 pandemic has significantly decreased due to the effectiveness of global vaccination and antiviral treatments. Nevertheless, immunocompromized patients with underlying conditions impairing their immune response to vaccines or natural infections are still at increased risk for COVID‐19‐associated morbidity and mortality 1,2 . States of relative immunologic vulnerability affect the severity of COVID‐19, making it crucial to find targeted approaches to manage different levels of clinical complexity.…”
Section: Introductionmentioning
confidence: 99%